UPAYA MENINGKATKAN HASIL BELAJAR PASSING ATAS DALAM PERMAINAN BOLA VOLI DENGAN METODE MENGAJAR DEMONSTRAN PADA SISWA KELAS VIII-B SMP NEGERI 39 MEDAN TA 2017/2018 - Arianus Lawolo (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to determine the improvement of Upper Passing Learning Outcomes in Volleyball Games with Demonstration Teaching Methods for Class VIII-B Students of SMP Negeri 39 Medan FY 2017-2018. Of the 39 students who took the test, there were 19 students (48.71%) who passed the KKM with a value range of 76-85 and an average score = 80. 28. The results achieved were that all students could pass the KKM with a range of values between 75-77 and an average value of 76. Thus, this study concludes that learning by using the demonstration teaching method can make a very large and significant contribution to the passing ability of volleyball in class VIII-B students of SMP Negeri 39 Medan in the 2017 academic year. /2018.